Administering multiple doses of a non N-(methylsuccinimido) anthranoyllycoctonine (MSAL)-containing tall larkspur (Delphinium occidentale) to cattle. (15th March 2017) - Welch, K.D.; Stonecipher, C.A.; Green, B.T.; Gardner, D.R.; Cook, D.; Pfister, J.A.
Abstract: Larkspurs ( Delphinium spp.) are a serious toxic plant problem for cattle in western North America. There are two chemotypes of D. occidentale, a more toxic and a less toxic chemotype. The objective of this study was to evaluate the acute toxicity of the less toxic chemotype when administered in multiple doses to cattle. These results suggest that cattle could consume enough of the less toxic chemotype to be poisoned in a range setting. Highlights: There are two chemotypes of D. occidentale, a more toxic and a less toxic chemotype. The less toxic chemotype of D. occidentale can be toxic to cattle. Multiple doses lower the toxic threshold of the less toxic chemotype of D. occidentale .